The asparagus genome sheds light on the origin and evolution of a young Y chromosome. Issue 1 (December 2017) - Harkess, Alex; Zhou, Jinsong; Xu, Chunyan; Bowers, John; Hulst, Ron; Ayyampalayam, Saravanaraj; Mercati, Francesco; Riccardi, Paolo; McKain, Michael; Kakrana, Atul; Tang, Haibao; Ray, Jeremy; et al.
Abstract Sex chromosomes evolved from autosomes many times across the eukaryote phylogeny. Several models have been proposed to explain this transition, some involving male and female sterility mutations linked in a region of suppressed recombination betweenX andY (orZ /W, U /V ) chromosomes. Comparative and experimental analysis of a reference genome assembly for a double haploidYY male garden asparagus (Asparagus officinalis L.) individual implicates separate but linked genes as responsible for sex determination. Dioecy has evolved recently withinAsparagus and sex chromosomes are cytogenetically identical with theY, harboring a megabase segment that is missing from theX . We show that deletion of this entire region results in a male-to-female conversion, whereas loss of a single suppressor of female development drives male-to-hermaphrodite conversion. A single copy anther-specific gene with a male sterileArabidopsis knockout phenotype is also in theY- specific region, supporting a two-gene model for sex chromosome evolution. Several models have been proposed to explain the emergence of sex chromosomes. Here, through comparative genomics and mutant analysis, Harkess et al. show that linked but separate genes on theY chromosome are responsible for sex determination inAsparagus, supporting a two-gene model for sex chromosome evolution.